Third All-Ukrainian Scientific and Practical Conference with International Participation “Theory and Practice of Modern Morphology” (Dnipro, 2019) - of journal "Morphologia", Editorial office (Морфологія / Morphologia / Morfologìâ, 2020)
On October 9-11, 2019, the Third All-Ukrainian Scientific and Practical Conference with International Participation "Theory and Practice of Modern Morphology" was held on the basis of the State Agency of State Administration "DMA". and clinical institutions in Ukraine and other countries. Television and the media began covering this event before the conference.